Fast-growing sunspot groups AR1618, AR1619, AR1620, AR1640 and their features - Fursiak, Yu.A. (Advances in Astronomy and Space Physics, 2013)
The paper considers evolutionary features of fast-growing sunspot groups AR1618, AR1619, AR1620, and AR1640. The study consists of the analysis of magnetic fields, movements of the solar atmosphere at different levels, and other data. In order to obtain the largest possible volume of information about the groups, data from a number of sources, both terrestrial (Kanzelhoehe Solar Observatory, Crimean Astrophysical Observatory), and space (SOHO, SDO, etc.) were used. A comparison of the groups with typical sunspot groups was made.